2008
DOI: 10.1128/mcb.01942-07
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the Basic Krüppel-Like Factor Gene (Klf3) Reveals a Role in Adipogenesis

Abstract: Krüppel-like factors (KLFs) recognize CACCC and GC-rich sequences in gene regulatory elements. Here, we describe the disruption of the murine basic Krüppel-like factor gene (Bklf or Klf3). Klf3 knockout mice have less white adipose tissue, and their fat pads contain smaller and fewer cells. Adipocyte differentiation is altered in murine embryonic fibroblasts from Klf3 knockouts. Klf3 expression was studied in the 3T3-L1 cellular system. Adipocyte differentiation is accompanied by a decline in Klf3 expression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
162
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(174 citation statements)
references
References 38 publications
(65 reference statements)
10
162
0
2
Order By: Relevance
“…Our data also show that lipid metabolism is important in CTBP-1 regulation of life span. Consistent with our demonstration of CTBP-1's involvement in lipid regulation, recent publications have documented a role for mammalian CtBP in regulating lipid storage and adipogenesis in mammalian cells and mice (47)(48)(49) while this manuscript was under review. Accumulation of lipid has been associated with aging-related diseases such as obesity, type II diabetes, insulin resistance and cancer (50,51).…”
Section: Resultssupporting
confidence: 62%
“…Our data also show that lipid metabolism is important in CTBP-1 regulation of life span. Consistent with our demonstration of CTBP-1's involvement in lipid regulation, recent publications have documented a role for mammalian CtBP in regulating lipid storage and adipogenesis in mammalian cells and mice (47)(48)(49) while this manuscript was under review. Accumulation of lipid has been associated with aging-related diseases such as obesity, type II diabetes, insulin resistance and cancer (50,51).…”
Section: Resultssupporting
confidence: 62%
“…The generation of a KLF3 knockout mouse has revealed a role for KLF3 in regulating adipogenesis (10). In this model, KLF3 expression was ablated by targeted deletion of a region within the C-terminal zinc finger DNA-binding domain.…”
Section: Klf3 and Adipogenesismentioning
confidence: 99%
“…In addition to the interaction with CtBP, full repression activity is dependent on sumoylation (6). Recent progress has begun to define the biology of KLF3, suggesting widespread roles in differentiation, including erythropoiesis, lymphopoiesis, and adipogenesis (7)(8)(9)(10). This review will describe the molecular structure of KLF3 in the context of the KLF family, the molecular mechanisms by which it regulates expression of its target genes and also the biological functions that have been recently attributed to this protein.…”
Section: Introductionmentioning
confidence: 99%
“…14 Previous reports showed that KLF proteins had different expression patterns during adipogenesis and several KLFs had been proved to either promote or inhibit this process. [15][16][17][18][19][20][21] Krü ppel-like factor 9 (KLF9), previously designated as basic transcription element-binding protein-1 (BTEB1), was initially isolated from a rat liver cDNA library. 22 KLF9 was further identified to be important for development and other physiological functions.…”
mentioning
confidence: 99%